Incidence of Βeta-Thalassemia Minor among Healthy Blood Donors - Mehwish Bibi, Saira Nasr Malik, Aizaz Afridi, Zakia Rehman, Zain Ul Abedien, Aamer Ali Khattak (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Disorders with a markedly slowed rate of globin chain synthesis are referred to as thalassemia. Hemoglobinopathy is a word used to describe diseases that cause structurally aberrant hemoglobin. Iron deficiency is seen in beta-thalassemia minor, which may change the typically increased HbA2 levels. According to World Health Organization (WHO) statistics, 7% of the global population carries a hemoglobin problem. Thalassemia is the most prevalent of the hemoglobinopathies, which are significant genetic issues in Pakistan. The prevalence of -thalassemia in Pakistan is around 5%, whereas the prevalence of hemoglobin S or E is between 0.5% and 1%. The purpose of the study was to determine how common beta thalassemia minor was among blood donors. Methods: A total of 500 individuals were recruited in this cross-sectional study who were referred for hemoglobin electro-phoresis between September 2015 and March 2016 were the subject of this investigation. A thorough clinical history was taken, including information on the patient’s age, sex, cast, family history, history of blood transfusions, and physical findings such as splenomegaly. Hb Electrophoresis tests were performed on all blood samples. Results: Out of total 500 patients, male were 83.1% (n=79) while female were 16.9% (n=16). Among total individuals, 18.3% (n=94) were found positive cases on Hb electrophoresis technique while remaining 406 patients were observed negative. All recruited individuals were categorised in four (04) different groups based on age; highest number of individuals were found in 18-30 years of age group with 69 patients, followed by 31-40 years of age group (n=19), 41-50 years of age group (n=5.3), and 51-60 years of age group (n=01). 94 (18.3%) had abnormal hemoglobin and beta thalassemia minor. Of them, 79 (84.4%) were men and 16 (17.2%) were women. Conclusion: Many groups in Pakistan continue to struggle with hemoglobin problems. Preventive interventions, such as pre-marriage carrier status identification and screening for beta thalassemia minor, are required to lower the incidence of beta thalassemia major by forcing couples with beta thalassemia minor to abort their pregnancies. Keywords: Hemoglobin Disorders, Thalassemia, β-Thalassemia, Healthy Blood Donors, Hemoglobinopathy